Oxytocin increases amygdala reactivity to threatening scenes in females - Lischke, Alexander; Gamer, Matthias; Berger, Christoph; Grossmann, Annette; Hauenstein, Karlheinz; Heinrichs, Markus; Herpertz, Sabine; Domes, Gregor (Psychoneuroendocrinology, 2012)
Summary - The neuropeptide oxytocin (OT) is well known for its profound effects on social behavior, which appear to be mediated by an OT-dependent modulation of amygdala activity in the context of social stimuli. In humans, OT decreases amygdala reactivity to threatening faces in males, but enhances amygdala reactivity to similar faces in females, suggesting sex-specific differences in OT-dependent threat-processing. To further explore whether OT generally enhances amygdala-dependent threat-processing in females, we used functional magnetic resonance imaging (fMRI) in a randomized within-subject crossover design to measure amygdala activity in response to threatening and non-threatening scenes in 14 females following intranasal administration of OT or placebo. Participants’ eye movements were recorded to investigate whether an OT-dependent modulation of amygdala activity is accompanied by enhanced exploration of salient scene features. Although OT had no effect on participants’ gazing behavior, it increased amygdala reactivity to scenes depicting social and non-social threat. In females, OT may, thus, enhance the detection of threatening stimuli in the environment, potentially by interacting with gonadal steroids, such as progesterone and estrogen.